2020
DOI: 10.1002/jcb.29569
|View full text |Cite
|
Sign up to set email alerts
|

The function of SNHG7/miR‐449a/ACSL1 axis in thyroid cancer

Abstract: Thyroid cancer (TC) has been characterized as the most common malignant malady of the endocrine system. Small nucleolar RNA host gene 7 (SNHG7) has been reported to serve as a key regulator in a large number of human cancer types, but its role in TC and the underlying regulatory mechanism have never been evaluated yet. The present study indicated that the expression of SNHG7 was markedly higher in TC cell lines. Knockdown of SNHG7 led to a suppression of TC cell progression and migration. Acyl‐CoA synthetase l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…SNHGs have been verified and involved in the progression of several endocrine-related cancers such as thyroid cancer, breast cancer, pancreatic cancer, and prostate cancer [34][35][36][37]. RT-qPCR has revealed the higher expression of SNHG11 in prostate cancer tissues and cell lines than in BPH and normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…SNHGs have been verified and involved in the progression of several endocrine-related cancers such as thyroid cancer, breast cancer, pancreatic cancer, and prostate cancer [34][35][36][37]. RT-qPCR has revealed the higher expression of SNHG11 in prostate cancer tissues and cell lines than in BPH and normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…In thyroid cancer (TC), lncRNASNHG7 is oncogenic, and SNHG7 requires long-chain acyl coenzyme A synthase 1 (ACSL1) to promote TC progression. miR-449a can bind both SNHG7 and ACSL1, and SNHG7 can act as a sponge for miR-449a, thus increasing ACSL1 in TC cells, so the SNHG7/miR449a/ACSL1 axis contributes to the proliferation and migration of TC cells [ 150 ]. In addition, the target gene acyl coenzyme synthase 4 (ACSL4), another member of the ACSL family, is a downstream target of miR-34a-5p and miR-204-5p in prostate cancer.…”
Section: Regulation Of Lipid Metabolism In the Tumor Microenvironmentmentioning
confidence: 99%
“…To analyze the role of miR-499a in the regulation of ACSL1 by SNHG7, researchers conducted RIP and luciferase reporter gene analyses. The experiment concluded that SNHG7 can be used as a sponge for miR-449a, thereby increasing ACSL1 in TC cells and promoting the proliferation and migration of TC cells [130]. Additionally, lncRNA NEAT1 is highly expressed in docetaxel-resistant prostate cancer patients and cell lines.…”
Section: Acyl-coa Synthetase Long Chain Family Membermentioning
confidence: 99%